Reducing poverty through agricultural sector strategies in eastern and southern Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Summary report of a workshop, Wageningen, the Netherlands, 23-25 November 1998.EC and CTA, 1999. 56 pp.ISBN 92 9081 2079CTA No 924, 10 credit points